Pest categorisation of Dendrolimus spectabilis. (10th November 2022) - ; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Dendrolimus spectabilis (Lepidoptera: Lasiocampidae), a moth, also known as the Japanese pine caterpillar, for the European Union (EU). D . spectabilis is native to China, Japan and Korea. Its larvae primarily feed on the needles of Pinus densiflora and P . thunbergii and can also feed on P . strobus, P . rigida, P . taeda and P. tabuliformis . The pest can have one or two generations per year; winter is mostly spent as fifth instar larvae in the soil. Adults emerge in July and August and females lay egg masses of 200–300 eggs on coniferous host needles. Natural enemies are described as significant factors of population density changes in Japan and the Republic of Korea. The pest can be detected visually, and there are morphological keys as well as molecular markers allowing identification. D. spectabilis could enter the EU, either as eggs, larvae or pupae in the foliage of plants for planting or cut branches, as larvae on wood with bark or as overwintering larvae in the litter of potted plants. However, Annex VI of Regulation 2019/2072 prohibits the introduction of D. spectabilis hosts from countries and areas where the pest occurs. D. spectabilis occurs in climatic zones that are found in the EU, and the fact that it attacks the North American P. strobus, P. taeda and P. rigida in its Asian native area suggests a potential to shift to local conifer species in the EU territory. There is uncertainty regarding the magnitude of economic and environmental impact of D. spectabilis on conifer species commonly occurring in the EU. Notwithstanding this uncertainty, D. spectabilis satisfies all the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest.